Three different types of plumbing system beneath the neighboring active volcanoes of Tolbachik, Bezymianny, and Klyuchevskoy in Kamchatka. Issue 5 (27th May 2017) - Koulakov, Ivan; Abkadyrov, Ilyas; Al Arifi, Nassir; Deev, Evgeny; Droznina, Svetlana; Gordeev, Evgeny I.; Jakovlev, Andrey; El Khrepy, Sami; Kulakov, Roman I.; Kugaenko, Yulia; Novgorodova, Anzhelika; Senyukov, Sergey; et al.
Abstract: The Klyuchevskoy group of volcanoes (KGV) in Kamchatka includes three presently active volcanoes (Klyuchevskoy, Bezymianny, and Tolbachik) located close together in an area of approximately 50 × 80 km. These three volcanoes have completely different compositions and eruption styles from each other. We have analyzed new data recorded by a temporary seismic network consisting of 22 seismic stations operated within the area of Tolbachik in 2014–2015 in conjunction with the data from the permanent network and the temporary PIRE network deployed at the Bezymianny volcano in 2009. The arrival times of the P and S waves were inverted using a local earthquake tomography algorithm to derive 3‐D seismic models of the crust beneath the KGV as well as accurate seismicity locations. High‐resolution structures beneath the Tolbachik volcanic complex were identified for the first time in this study. The tomography results reveal three different types of feeding system for the main KGV volcanoes. The basaltic lavas of the Klyuchevskoy volcano are supplied directly from a reservoir at a depth of 25–30 km through a nearly vertical pipe‐shaped conduit. The explosive Bezymianny volcano is fed through a dispersed system of crustal reservoirs where a lighter felsic material separates from the mafic component and ascends to the upper crust to form andesitic magma sources. For Tolbachik, low‐viscosity volatile‐saturated basalts ascend from two deep reservoirs following a system of fractures in the crust associated with the intersections of regional faults. Plain Language Summary: The Klyuchevskoy group of volcanoes (KGV) in Kamchatka includes three presently active volcanoes (Klyuchevskoy, Bezymianny, and Tolbachik) located close together in an area of approximately 50 × 80 km. These three volcanoes are among the most active volcanoes in the world, and they have completely different compositions and eruption styles from each other. We have analyzed new data recorded by a temporary seismic network consisting of 22 seismic stations installed within the area of Tolbachik in 2014–2015 in harsh natural conditions. Based on these data, we have derived high‐resolution structures beneath the Tolbachik volcanic complex and surrounding areas. The tomography results reveal three different types of feeding system for the main KGV volcanoes. The basaltic lavas of the Klyuchevskoy volcano are supplied directly from a reservoir at a depth of 25–30 km through a nearly vertical pipe‐shaped conduit. The explosive Bezymianny volcano is fed through a dispersed system of crustal reservoirs where a lighter felsic material separates from the mafic component and ascends to the upper crust to form andesitic magma sources. For Tolbachik, low‐viscosity volatile‐saturated basalts ascend from two deep reservoirs following a system of fractures in the crust associated with the intersections of regional faults. Key Points: A new crustal seismic model is constructed for Tolbachik and adjacent volcanoes Seismicity beneath Klyuchevskoy reflects a straight conduit that brings magma directly from the mantle The Bezymianny volcano is fed through separating felsic magma and volatiles from midcrustal sources